The fish detective: moone boy - O'Dowd, Chris (London : Mcmillan, 2015)
Martin Moone loves Christmas but this year family Moone is on a budget, and Martins gift list is bein downsized. If he wants a game boy, he's going to have to work for it. So his imaginary friend Sean, suggests he get a job ...